2014
DOI: 10.1530/eje-14-0258
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of NPH insulin, insulin detemir, and insulin glargine on the GH–IGF1–IGFBP axis in patients with type 1 diabetes

Abstract: Objective: Insulin regulates the GH-IGF1 axis. Insulin analogs differ from human insulin in receptor affinity and possibly liver accessibility. Therefore, we compared the GH-IGF1 axis response with human NPH insulin, insulin detemir, and insulin glargine in patients with type 1 diabetes (T1D). Methods: A total of 17 patients (seven were women) with T1D (age of 42 (24-63) 3) mg/l!h), but in the highest AUC of bioactive IGF (3.8 (3.5-4.2) vs 3.7 (3.4-4.0) vs 4.4 (4.1-4.8) mg/l!h) (all P!0.01). These differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In vivo a single dose of IDet in relation to NPH or IGla was found to cause higher levels of bioactive IGF1 but not total IGF1. This finding was accompanied by a larger suppression of IGFBP1 with consecutive lower GH concentrations 8 . Other studies reported no differences between IDet and NPH or IDet and IGla regarding the GH‐IGF1‐IGFBP axis 20,21 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In vivo a single dose of IDet in relation to NPH or IGla was found to cause higher levels of bioactive IGF1 but not total IGF1. This finding was accompanied by a larger suppression of IGFBP1 with consecutive lower GH concentrations 8 . Other studies reported no differences between IDet and NPH or IDet and IGla regarding the GH‐IGF1‐IGFBP axis 20,21 .…”
Section: Discussionmentioning
confidence: 86%
“…Due to its liver specificity, IDet might partially compensate portal insulinopenia and thereby GH hypersecretion. Recent reports suspected that this has a favorable impact on weight gain 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Detemir has a myristic (C14) acid substitution at a terminal B29 lysine (no threonine), and its slow action is attributable to hydrophobic self-association in tissues and also to binding of the acyl chain to fatty acid binding sites on serum albumin. 6,20 A further flattened profile is associated with degludec (t1/2 ~25 hours, duration >40 hours) and is enabled because, despite its superficial similarity to detemir, its des-30-structure (again no threonine) forms very long unique hexameric sequences stabilised by zinc, phenol and hydrophobic contact between covalently attached hexadecanoic (C16) diacid chains linked at B29 with glutamic acid. 9,19 These lipophilic agents therefore differ from an alternative soluble long-acting insulin, glargine, which has a replacement of glycine for asparagine at position A21 and addition of two arginine molecules at positions B29-30.…”
Section: Development Of Injectable Insulins For Intensive Control Reg...mentioning
confidence: 99%
“…Such effects have been observed with intraperitoneal insulin infusions, 10,11,72 direct intraportal insulin administration, 13 and hepatoselective insulins, as well as with long-acting parenteral insulin with a circulating depot, such as insulin detemir, which appears to possess an increased liver specificity. 18,71,73 Insulin increases the sensitivity of the liver to growth hormone (GH) by upregulating GH receptor expression, thereby augmenting insulin-like growth factor-1 (IGF-1) production. 74 In addition, it downregulates IGF binding protein-1 (IGFBP-1) production in the liver, thereby increasing circulating IGF-1 bioactivity.…”
Section: Potential Benefits Of Portal Insulin Administration Beyond Gmentioning
confidence: 99%